Fundamental study of taphole clay behaviour with respect to the binder system and evaluation of alternative non-toxic binders - Garbers-Craig, Andrie Mariana (University of Pretoria, 2024)
Thesis (PhD (Metallurgical Engineering))--University of Pretoria, 2024.